FORMATION OF PRODUCT STRATEGY AS THE MAIN ELEMENT OF MARKETING PRODUCT POLICY (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Today, when the target market changes, competition increases or the marketing environment changes, the nature and pace of product development must also change. Different markets and competitive situations require different product development cycle lengths, degrees of standardization and support services. All of the above requires a rethinking of the role of marketing product policy, in particular marketing product strategy.The purpose of the article.To investigate the essence of the product strategy, the peculiarities of product marketing, to analyze the foreign experience of forming a product strategy and to build a model of the company's product marketing strategy.Metods. The use of the method of analysis and synthesis of foreign experience in the formation of product marketing made it possible to adapt the model of the company's product marketing strategy to domestic realities.Results A product strategy sets the direction for the business, unites everyone around common goals and reduces waste. Product marketers spend a lot of time solving problems – many of which could be avoided if product goals, priorities and strategies were clear and aligned. In order to better understand who should do what, a model of the company's marketing product strategy is proposed, which includes three components: a strategy for determining product activity (initial activity); product manufacturing strategy (input activity) and sales strategy (output activity).Conclusiоns The structure of product marketing and its functioning depends on the size of the enterprise, the markets in which it operates, as well as the skills and preferences of the people involved. However, in order to achieve success, it is necessary to realize three aspects: decide who and what should be done;  understand who is ultimately responsible for the success of each product;  a detailed understanding of existing and potential customers and markets. Knowing this helps ensure products are well positioned, customers want to buy them, and sales teams have what they need to sell.
Keywords: product, product marketing, marketing product strategy, marketing product policy, strategic portfolio of the enterprise